1996
DOI: 10.1063/1.361025
|View full text |Cite
|
Sign up to set email alerts
|

Plasma properties determined with induction loop probes in a planar inductively coupled plasma source

Abstract: Electromagnetic fields in a planar rf inductively coupled plasma source, of interest for materials processing, were measured using a two-loop inductive ͑B-dot͒ probe. The two loops were oriented to measure the time derivative of the axial and radial components of the magnetic field Ḃ z and Ḃ r , respectively, at various positions in the r -z plane of the cylindrically symmetric argon discharge. Maxwell's equations were used with this data to calculate amplitudes of the rf azimuthal electric field E and current… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

1997
1997
2003
2003

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…The electron density shown in figure 5(a) increases from the centre plane of the discharge and peaks at roughly r/R = 0.5. As discussed by Hopwood et al [22], Meyer and Wendt [23] and Meyer et al [24] the inductive electric field and thus the absorbed power peak at approximately one-half the radius of the coil and go to zero in the centre of the discharge. The effective electron temperature, shown in figure 5(b), increases slightly towards the chamber wall.…”
Section: Resultsmentioning
confidence: 91%
“…The electron density shown in figure 5(a) increases from the centre plane of the discharge and peaks at roughly r/R = 0.5. As discussed by Hopwood et al [22], Meyer and Wendt [23] and Meyer et al [24] the inductive electric field and thus the absorbed power peak at approximately one-half the radius of the coil and go to zero in the centre of the discharge. The effective electron temperature, shown in figure 5(b), increases slightly towards the chamber wall.…”
Section: Resultsmentioning
confidence: 91%
“…For example, measurements of electron drift velocities in the skin layer of an ICP reactor at 10 and 50 mTorr by Meyer et al were found to be comparable to the local electron thermal velocities, which suggests that the AEEDs were considerably anisotropic. 16 Kolobov et al computationally investigated the angular distribution of electrons in an ICP having a coaxial solenoidal coil. 17 They found that the angular distribution of electrons with energies above the plasma potential was anisotropic in the radialaxial (rz) plane and that this anisotropy depends on the radial position ͑distance from the coil͒.…”
Section: Introductionmentioning
confidence: 99%
“…Electromagnetic field measurements have been reported for planar inductively coupled discharges [5][6][7]. Hopwood et al [5] measured the magnitude of the magnetic induction to be in the range of 0.2-0.7 mT at the window and to decay exponentially as a function of distance from the window.…”
Section: Introductionmentioning
confidence: 99%